1978
DOI: 10.1002/chin.197840043
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: RAMAN SPECTROSCOPIC STUDY OF COBALT‐MOLYBDENUM Γ‐ALUMINA CATALYSTS

Abstract: Die Strukturen der Mound Co‐Spezies in Co‐Mo/y‐Al,O3‐Katalysatorsystemen werden mit Hilfe der Laser‐ Raman‐Spektroskopie untersucht.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
1

Year Published

1982
1982
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 1 publication
1
21
0
1
Order By: Relevance
“…% corresponds to a theoretical molybdate monolayer on the y-A1 2 0 3 support used. At decreasing loading in the submonolayer range, the surface concentration of the polymolybdate species is reduced in favor of a distorted monomeric tetrahedral MoO; -species [310,316].…”
Section: C) Raman Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations
“…% corresponds to a theoretical molybdate monolayer on the y-A1 2 0 3 support used. At decreasing loading in the submonolayer range, the surface concentration of the polymolybdate species is reduced in favor of a distorted monomeric tetrahedral MoO; -species [310,316].…”
Section: C) Raman Spectroscopymentioning
confidence: 99%
“…Supported molybdate catalysts promoted by Ni2+ [313,314] and C0 2 + [312, [315][316][317][318] have been studied by Raman spectroscopy and Sombret et al [320] have applied the Raman microscope technique to obtain information about the spatial distribution of surface species and compounds. Other supported oxide catalysts have equally successfully been characterized by their Raman spectra in the low frequency region, namely tungsten oxide on y-A1 2 0 3 [321,322], rhenium oxide on alumina [323], and vanadium oxide on alumina [324,325].…”
Section: C) Raman Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the transition metal content of the catalysts influences the relative amounts of the various species (8, 12,13,21). This is the reason why in this study the active-phase concentration has been varied to a large extent.…”
Section: Introductionmentioning
confidence: 99%
“…[37] The band around 990 cm À1 shifted towards higher wavenumbers upon increasing the calcination temperature, which could be due to a shorter Mo¼O bond and more severe structural distortion. [28,29] The increase in relative intensity indicated a higher coverage of these molybdate species.…”
mentioning
confidence: 98%